Against besieged literature: fictions, obsessions and globalisations of Chinese literature - Carles Prado-Fonts (Digithum, 2008)
Chinese literature in the 20th century has seen how the combination between, on one hand, the canon established by Socialist realism in China and, on the other, the approaches of Area Studies in the West imposed a limited vision and a partial and slanted assessment of its complexity. The article defends the fact that it is essential to recover the literariness of the literary text, appealing to the sophistication and critical capacity of readers, as a basic strategy for liberating Chinese literature from the interpretive siege that constrains it. The article analyses the interrelation of various aspects -such as the confusion between reality and fiction, the obsessions for interpretations of a national allegorical nature or other mechanisms of globalisation and self-Orientalism- that, in an interrelated way, determine the production and circulation of modern and contemporary Chinese literature in the global literary system. The novel Fortress Besieged by the writer Qian Zhongshu is a paradigmatic example of this situation.